If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6) + -4 = 0 Reorder the terms: 3(6 + x) + -4 = 0 (6 * 3 + x * 3) + -4 = 0 (18 + 3x) + -4 = 0 Reorder the terms: 18 + -4 + 3x = 0 Combine like terms: 18 + -4 = 14 14 + 3x = 0 Solving 14 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 3x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 3x = 0 + -14 3x = 0 + -14 Combine like terms: 0 + -14 = -14 3x = -14 Divide each side by '3'. x = -4.666666667 Simplifying x = -4.666666667
| 44=2a+b | | 5a-a+4a=32 | | y=3cos(-pi/2) | | 3cos(2*0-pi/2)=y | | 5y+1=4y-2 | | 3+4x=-y | | 3cos(-pi/2) | | 3cos(2*1-pi/2) | | 2x^5-2x^2+x-1=0 | | 3cos(2*0-pi/2) | | 7h+2+3h+5= | | 3cos(2(0)-pi/2) | | 4ab-6b= | | 7n+5=25 | | 3x(x+1)-6=15 | | 11xy+xy= | | 2(x-13)=14 | | h^2-5h-70=0 | | -4(6+3s)=6+5s | | 4(6+3s)=6+5s | | 4*(6+3s)=6+5s | | y^3+3y^2-17y+1=0 | | z^2+(5-3i)z+4-7i=0 | | ydx-(y^2-2x)dy=0 | | 3(x+2)=x+20 | | 4x(6+3s)=6+5s | | 7-4x(6+3s)=6+5s | | x^2-2y^2=13 | | 1-(3p-1)/2=p/3 | | 5c+12=27 | | 3(x+1)+2(x-4)=2x-(x-6) | | 2(x+3)-4x=0.5(x+2) |